(untitled) (REMUNOM, 2023)
The main objective of this work is to examine the possibility of psychopaths being partially responsible according to the Brazilian Penal Code. Psychopathy is seen by specialists as a way of life, an intrinsic aspect of the individual. Psychopaths are not carriers of any disease or mental retardation and, therefore, are not considered unaccountable, as provided in article 26 of the CP. That article refers to cases in which an individual’s intelligence and willpower are impaired, which is not the case with psychopaths, who are fully aware of their actions. However, some jurists argue that semi-imputability may apply if the defendant is unable to make a decision due to his mental disorder, specifically when he is unable to determine the wrongful nature of his actions. In these cases, semi-imputability should only be considered if there is a clear deficit in the individual’s ability to assess himself and make ethical judgments.